2019
DOI: 10.3390/nu11040890
|View full text |Cite
|
Sign up to set email alerts
|

From Probiotics to Psychobiotics: Live Beneficial Bacteria Which Act on the Brain-Gut Axis

Abstract: There is an important relationship between probiotics, psychobiotics and cognitive and behavioral processes, which include neurological, metabolic, hormonal and immunological signaling pathways; the alteration in these systems may cause alterations in behavior (mood) and cognitive level (learning and memory). Psychobiotics have been considered key elements in affective disorders and the immune system, in addition to their effect encompassing the regulation of neuroimmune regulation and control axes (the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 130 publications
(211 reference statements)
1
85
0
12
Order By: Relevance
“…Gut microbiota, like a virtual endocrine organ, reacts to various internal and external stimuli [5, [75][76][77][78]. Consequently, gut microbiota influences and regulates hosts' health and mood statue including aggression by integrating metabolic, immune, endocrine, and neural reactions through the bidirectional communication of the gut-brain axis (Figure 1) [7, 33,[79][80][81][82][83]. Gut microbiota in hosts, for example, regulates brain neurotransmitters [84][85][86][87] such as serotonin (5-HT) through releasing its precursor, tryptophan, an essential amino acid [75,[88][89][90].…”
Section: Gut Microbiota and The Gut-brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota, like a virtual endocrine organ, reacts to various internal and external stimuli [5, [75][76][77][78]. Consequently, gut microbiota influences and regulates hosts' health and mood statue including aggression by integrating metabolic, immune, endocrine, and neural reactions through the bidirectional communication of the gut-brain axis (Figure 1) [7, 33,[79][80][81][82][83]. Gut microbiota in hosts, for example, regulates brain neurotransmitters [84][85][86][87] such as serotonin (5-HT) through releasing its precursor, tryptophan, an essential amino acid [75,[88][89][90].…”
Section: Gut Microbiota and The Gut-brain Axismentioning
confidence: 99%
“…Probiotics (also called psychobiotics or bio-friendly agents), defined "as a source of live (viable) naturally occurring microorganisms (direct-fed microbials, DFMs)", have been used as dietary supplements to target gut microbiota (microbiome) for a novel promising therapeutic approach of various diseases including social stressinduced mental disorders in humans and various experimental animals [27][28][29][30][31][32][33][34][35][36]. Different probiotic strains, for example, have been investigated as functional food or therapeutic treatment of various diseases, including Bifidobacterium bifidum [37][38][39]; Bifidobacterium bifidum (BGN4) and Bifidobacterium longum (BORI) [40,41]; Bifidobacterium pseudocatenulatum [42]; Lactobacillus helveticus [31,32]; Lactobacillus plantarum [43]; Lactobacillus paracasei (KW3110, [44]); Lactobacillus rhamnosus [45]; and Clostridium butyricum [46].…”
Section: Introductionmentioning
confidence: 99%
“…This bidirectional regulation is accomplished via complex neuroendocrine pathways (Khalil et al, 2019). The gut microbiota can adjust these pathways by regulating the levels of neurotransmitters and inflammatory factors and affecting the hypothalamic-pituitaryadrenal axis (Bermúdez-Humarán et al, 2019). Therefore, abnormal intestinal flora composition may lead to abnormal neurotransmitter secretion, which may promote the development of neuropsychiatric diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Gut physiology (8,9) Nutrient production and absorption (10) Host development and physiology (11) Energy balancing (12) Metabolic functions (13,14) Immune system functions (15)(16)(17) Inflammatory processes (18) Neurons-brain-behavior system (19)(20)(21)(22) The majority of those studies cited here have demonstrated improvement in the clinical status of patients after targeted intervention influencing the gut microbiota. Similar studies relatively recently have led to definition of the so-called microbiome-gut-brain axis.…”
Section: Kubelkova Macela: Microbiota-gut-brain Axis 42 Box 2: Biolomentioning
confidence: 97%